The Only Thing That Stops a Guy with a Bad Policy is a Guy with a Good Policy: An Examination of the NRA’s “National School Shield” Proposal - Burton, Catherine E. (2013)
With the recent tragedy at Sandy Hook Elementary in Newtown, CT, the public and the government are looking for solutions to school violence. The National Rifle Association (NRA), a Second Amendment, pro-gun advocacy group, has proposed an “education and training emergency response program” called The National School Shield, which advocates the placement of armed security in schools. Although the program sounds provocative, serious questions complicate its plausibility, necessity, motive, and effectiveness. Furthermore, the potential policy and practical ramifications of encouraging armed security forces in U.S. schools are complex. The authors examined the proposal’s key elements from a public policy perspective and determined that the NRA program would be expensive in terms of both implementation and civil and/or criminal liability, would increase juvenile contact with the criminal justice system, would increase the potential for injuries and deaths from firearms, and would potentially only serve to increase profits for those invested in security industries. More potentially effective and safe policy alternatives are offered